Mind Mapping Bagi Start-up Business Sektor UMKM Dalam Mendukung Pengembangan Potensi Wisata Di Kecamatan Doro Kabupaten Pekalongan Dengan Smart Business Map (SBM) - Sabana, Choliq; Prasetyani, Titi Rahayu; Kushermanto, Andi; Tsamara, Tsamara (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2026)
Doro District is a sub-district in Pekalongan Regency, Central Java Province, which is approximately 15 km from the Capital City of Pekalongan Regency to the east with its administrative center in Doro Village. Doro District has natural resource potential which prospects for further development in the natural tourism sector. The development of creative tourism must certainly be supported by other supporting sectors, one of which is the processed food culinary sector. However, the obstacle is how to develop this processed food culinary sector which can become a source of income for local residents, starting with building an entrepreneurial mindset. One way is with the mind mapping method to start a business. Therefore, this service activity is directed at training in building mind mapping for start-up businesses, especially processed food MSMEs with the Smart Business Map (SBM) and Business Management learning model.